Laparoscopy is safe among patients with congestive heart failure undergoing general surgery procedures - Speicher, Paul J. (Surgery, 2014)
BACKGROUND: Over the past 2 decades, laparoscopy has been established as a superior technique in many general surgery procedures. Few studies, however, have examined the impact of the use of a laparoscopic approach in patients with symptomatic congestive heart failure (CHF). Because pneumoperitoneum has known effects on cardiopulmonary physiology, patients with CHF may be at increased risk. This study examines current trends in approaches to patients with CHF and effects on perioperative outcomes. METHODS: The 2005–2011 National Surgical Quality Improvement Program Participant User File was used to identify patients who underwent the following general surgery procedures: Appendectomy, segmental colectomy, small bowel resection, ventral hernia repair, and splenectomy. Included for analysis were those with newly diagnosed CHF or chronic CHF with new signs or symptoms. Trends of use of laparoscopy were assessed across procedure types. The primary endpoint was 30-day mortality. The independent effect of laparoscopy in CHF was estimated with a multiple logistic regression model. RESULTS: A total of 265,198 patients were included for analysis, of whom 2,219 were identified as having new or recently worsened CHF. Of these patients, there were 1,300 (58.6%) colectomies, 486 (21.9%) small bowel resections, 216 (9.7%) ventral hernia repairs, 141 (6.4%) appendectomies, and 76 (3.4%) splenectomies. Laparoscopy was used less frequently in patients with CHF compared with their non-CHF counterparts, particularly for nonelective procedures. Baseline characteristics were similar for laparoscopy versus open procedures with the notable exception of urgent/emergent case status (36.4% vs 71.3%; P < .001). After multivariable adjustment, laparoscopy seemed to have a protective effect against mortality (adjusted odds ratio, 0.45; P = .04), but no differences in other secondary endpoints. CONCLUSION: For patients with CHF, an open operative approach seems to be utilized more frequently in general surgery procedures, particularly in urgent/emergent cases. Despite these patterns and apparent preferences, laparoscopy seems to offer a safe alternative in appropriately selected patients. Because morbidity and mortality were considerable regardless of approach, further understanding of appropriate management in this population is necessary.